THE CORRELATION OF TEACHER PERSONALITY COMPETENCE WITH DISCIPLINE OF GRADE 6 STUDENT - Siti Animah; Sholeh Hidayat; Lukman Nulhakim (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The background of this research is the low awareness of discipline. This study aims to determine the correlation of teacher personality competence with student discipline and how much the correlation between teacher competency and student discipline. The research method used was correlational. This research was conducted in grade 6 SDN Majalaya with the sample of 30 students. Data collection techniques were Likert scale questionnaires that had been tested for validity andreliability. Based on the results of the correlation analysis test obtained a correlation coefficient of 0.61 with a significance of 0.000. The significance value obtained was 0.000. 0.000 <0.05 thus there was a correlation between the teacher's personal competence and student discipline.